2022
DOI: 10.3389/fimmu.2022.831849
|View full text |Cite
|
Sign up to set email alerts
|

An Autoantigen Atlas From Human Lung HFL1 Cells Offers Clues to Neurological and Diverse Autoimmune Manifestations of COVID-19

Abstract: COVID-19 is accompanied by a myriad of both transient and long-lasting autoimmune responses. Dermatan sulfate (DS), a glycosaminoglycan crucial for wound healing, has unique affinity for autoantigens (autoAgs) from apoptotic cells. DS-autoAg complexes are capable of stimulating autoreactive B cells and autoantibody production. We used DS-affinity proteomics to define the autoantigen-ome of lung fibroblasts and bioinformatics analyses to study the relationship between autoantigenic proteins and COVID-induced al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 283 publications
0
9
0
Order By: Relevance
“…Several papers show a striking relationship to human autoimmunity; 100−103 an analysis of human lung cells showed that a large number of COVID-dysregulated proteins during acute infection are known human autoantigens. 104 Finally, the HPP Pathology mission is to enhance education and outreach for physicians and healthcare providers worldwide, raise awareness about proteomics, provide education through meetings and tutorials, and increasingly bring international…”
Section: Pillarmentioning
confidence: 99%
“…Several papers show a striking relationship to human autoimmunity; 100−103 an analysis of human lung cells showed that a large number of COVID-dysregulated proteins during acute infection are known human autoantigens. 104 Finally, the HPP Pathology mission is to enhance education and outreach for physicians and healthcare providers worldwide, raise awareness about proteomics, provide education through meetings and tutorials, and increasingly bring international…”
Section: Pillarmentioning
confidence: 99%
“…consequent generation of autoantibodies (169,170). The analysis of the "autoantigenicoma" in patients who suffered from COVID-19 through the detection of autoantigens bound to determatan sulfate (autoantigen-DS complex) seems to be helpful to predict the appearance of autoimmune diseases and neurological damage (171,172). Using this strategy, 751 autoantigen candidates were found, of which 657 are directly altered by infection with SARS-CoV-2.…”
Section: Role Of the Dysregulated Antibodies Response Against Sars-co...mentioning
confidence: 99%
“…Regarding the nervous system, 150 autoantigens of proteins are related to axon guidance, neuron projection, myelin sheath, axon growth cone, neuronal cell body, cerebellar Purkinje cell layer, peripheral nervous system axon regeneration, radial glial scaffolds and proteins related to the olfactory bulb. There were also 193 autoantigens of proteins related to neurological diseases such as neuronal infection with Japanese encephalitis virus, neuroblastoma, glioblastoma, neurodegeneration in Down syndrome, AD, schizophrenia, cerebral ischemia induced neurodegenerative diseases, PD, and neurodegeneration (Supplementary Table 2) (172). The mechanism by which coronaviruses could resemble conditions of early events of neurodegeneration should be explored considering the participation of the immune system and the uncontrolled generation of autoantibodies that deteriorate neuronal circuits.…”
Section: Role Of the Dysregulated Antibodies Response Against Sars-co...mentioning
confidence: 99%
“…COVID-19 is no exception with clinical syndromes such as autoimmune cytopenia, Guillain-Barre syndrome, autoimmune encephalitis, lupus and acquired haemophilia being reported (12). COVID-19 infection results in the post-translational modification of a vast number of proteins with high intrinsic propensity to become autoantigens, offering an explanation for the diverse autoimmune complications observed (13).…”
Section: Discussionmentioning
confidence: 99%